2009
DOI: 10.1177/0886260509354585
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Relationship Factors That Differentiate Female Offenders With and Without a Sexual Abuse History

Abstract: The link between prior sexual abuse and female offending is one of the most consistent findings within the etiology of female offending. It is not, however, part of every female offender's life history. Working from research on the impact of abuse on individuals, the current article examines the individual and relationship factors that differentiate female offenders (n = 131) with a history of sexual abuse and female offenders without a history of sexual abuse. Results from chi-square, t test, and logistic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 47 publications
(56 reference statements)
0
13
0
Order By: Relevance
“…The nature of and pathways to offending may also be different for females than for males (Jones et al ; Steffensmeier and Allan ). For example, responding to sexual and other physical abuse seems to be a key reason females turn to crime (Chesney‐Lind and Rodriquez ; Hubbard and Pratt ; McCartan and Gunnison ; Salisbury and Van Voorhis ). However, legitimate outlets for females to escape abusive situations could alleviate some of the growth in female offending.…”
Section: The Importance Of a Focus On Female Offendersmentioning
confidence: 99%
“…The nature of and pathways to offending may also be different for females than for males (Jones et al ; Steffensmeier and Allan ). For example, responding to sexual and other physical abuse seems to be a key reason females turn to crime (Chesney‐Lind and Rodriquez ; Hubbard and Pratt ; McCartan and Gunnison ; Salisbury and Van Voorhis ). However, legitimate outlets for females to escape abusive situations could alleviate some of the growth in female offending.…”
Section: The Importance Of a Focus On Female Offendersmentioning
confidence: 99%
“…Females now account for one third (33.58%) of all arrests for Part I crimes, up from just 10 years ago when they accounted for 28.37% (FBI, 2015). There is also some evidence that female offenders may be systematically different from male offenders in the nature of the crimes they commit (with disproportionate involvement in prostitution and drug crimes), as well as the fact that female offending often has origins in physical or sexual abuse and the search for coping mechanisms (Chesney-Lind & Rodriquez, 1983; Hubbard & Pratt, 2002; McCartan & Gunnison, 2010; Salisbury & Van Voorhis, 2009). The criminal justice system could represent a prosocial alternative for females trying to escape negative situations.…”
mentioning
confidence: 99%
“…Research which examines abuse as a form of strain should seek to differentiate between individuals who experience emotional/verbal, sexual, and physical abuse, or more than of those types of abuse, as there may be different identifiable consequences associated with each. For example, past research has suggested that childhood sexual abuse is an important predictor for involvement in the criminal justice system and abusive relationships (McCartan & Gunnison, 2010). Finally, researchers should attempt to operationalize strain in diverse ways and utilize additional data sources to further examine strain (e.g.…”
Section: Discussionmentioning
confidence: 99%